Pola Permukiman Tepi Sungai Kota Jambi - Harlia Febrianti (JOURNAL VISION TECHNOLOGY (V-TECH), 2023)
The city of Jambi in its history is inseparable from its relationship with the Batanghari River, even in the history of the establishment of the city of Jambi it is told that the founders of Jambi City traced the river from upstream to downstream and then settled in a place which later became the forerunner of Jambi City. This study attempts to provide an overview of the pattern of riverside settlements in the city of Jambi. This objective is based on an attempt to reveal the pattern of riverside settlements in the city of Jambi. The aim of this research was achieved by conducting field observations and map analysis. The results showed that the pattern of settlements along the river in Jambi City has a relationship with the character of the Batanghari River. The patterns found in this study are scattered, clustered and elongated patterns. Further research is needed to look at the development of riverside settlement patterns concerning other factors such as politics as well as social and economics.